Diversity and Inclusion in Clinical Trials: Global and Regional Perspectives (International Journal of Scientific Research in Science and Technology, 2025)
Clinical trials are the cornerstone of evidence-based medicine, yet persistent gaps in diversity and inclusion (D&I) threaten the generalizability, equity, and ethical integrity of medical research. Underrepresentation of racial, ethnic, gender, socioeconomic, and age groups may result in treatments that are ineffective or unsafe for certain populations. This paper presents a comprehensive analysis of D&I in clinical trials from global and regional perspectives. It explores the historical context, examines existing challenges and systemic barriers, and highlights emerging trends, regulatory developments, and community-driven initiatives aimed at improving representation. The discussion emphasizes the need for inclusive research practices to ensure that medical innovations are safe, effective, and equitable across all population groups. Future directions focus on strengthening policy frameworks, enhancing recruitment strategies, and fostering trust through culturally sensitive engagement.